2006
DOI: 10.4049/jimmunol.176.12.7645
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Transmodulates Monocyte Adhesion and Transmigration via Rac1- and PI3K-Mediated Inside-Out Signaling in Response toPorphyromonas gingivalisFimbriae

Abstract: We present evidence for a novel TLR2 function in transmodulating the adhesive activities of human monocytes in response to the fimbriae of Porphyromonas gingivalis, a pathogen implicated in chronic periodontitis and atherosclerosis. Monocyte recruitment into the subendothelium is a crucial step in atherosclerosis, and we investigated the role of P. gingivalis fimbriae in stimulating monocyte adhesion to endothelial cells and transendothelial migration. Fimbriae induced CD11b/CD18-dependent adhesion of human mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 60 publications
6
137
1
3
Order By: Relevance
“…CR3 exploitation by P. gingivalis is initiated at the level of TLR2, since TLR2 inside-out signaling is required for effective interaction of P. gingivalis fimbriae with CR3 (Harokopakis et al, 2006;Harokopakis and Hajishengallis, 2005). Consistent with this, we have now found that the intracellular survival of fimbriated P. gingivalis is dramatically reduced in TLR2-deficient macrophages relative to normal controls (Fig.…”
Section: Cr3 Exploitation By P Gingivalis Depends On Tlr2supporting
confidence: 81%
See 3 more Smart Citations
“…CR3 exploitation by P. gingivalis is initiated at the level of TLR2, since TLR2 inside-out signaling is required for effective interaction of P. gingivalis fimbriae with CR3 (Harokopakis et al, 2006;Harokopakis and Hajishengallis, 2005). Consistent with this, we have now found that the intracellular survival of fimbriated P. gingivalis is dramatically reduced in TLR2-deficient macrophages relative to normal controls (Fig.…”
Section: Cr3 Exploitation By P Gingivalis Depends On Tlr2supporting
confidence: 81%
“…The ability of P. gingivalis fimbriae to activate TLR2 inside-out signaling for CR3 activation suggested that this pathogen may stimulate monocyte transmigration. Indeed, we found that fimbriated P. gingivalis (or purified fimbriae) stimulate CR3-dependent monocyte adhesion to endothelial ICAM-1 and transmigration across endothelial cell monolayers (Harokopakis et al, 2006). This may represent a potentially protective mechanism which can contribute to monocyte recruitment to sites of P. gingivalis infection.…”
Section: P Gingivalis Stimulates Cr3-dependent Transendothelial Migrmentioning
confidence: 73%
See 2 more Smart Citations
“…Apart from its well accepted role as an oral pathogen in the establishment of chronic inflammation at the site of infection, there is increasing evidence of a link between P. gingivalis-associated periodontal disease and systemic inflammatory conditions, such as diabetes, preterm birth, aspiration pneumonia and atherosclerotic cardiovascular disease (Brodala et al, 2005;Liao et al, 2009;Lin et al, 2003;Maekawa et al, 2011;Pussinen and Mattila, 2004). On the cellular level, a convincing body of evidence indicates that P. gingivalis possesses unique signalling properties, which enable it to evade, subvert or manipulate the host immune defences by exploiting the toll-like receptor (TLR) family, in particular TLR2 (Burns et al, 2006;Hajishengallis et al, 2002;Hajishengallis et al, 2008b;Harokopakis et al, 2006;Wang et al, 2010). As an opportunistic pathogen, P. gingivalis can preferentially target innate immunity, which may in turn disable adaptive immunity, hence causing a general deregulation of the immune responses (Hajishengallis, 2009;Hajishengallis et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%